"A Horrible Interspecies Awkwardness Thing": (Non)Human Desire in the Mass Effect Universe. (February 2016) - Zekany, Eva
Canadian video game developer BioWare's critically acclaimed Mass Effect video game series has been called the most important science fiction universe of a generation. Whether or not one is inclined to agree, it cannot be denied that Mass Effect matters. It matters not only because of its brilliant narrative and the difficult questions it asks, but also because, as bioethicist Kyle Munkittrick writes, it reflects society as a whole. Mass Effect is a sci-fi epic in the truest sense, spanning over years and across hundreds of planets tucked away in the darkest corners of the galaxy, populated with dozens of species with their own histories, beliefs, cultures, and technologies. Academics and dedicated fans have explored the numerous facets of the game, from its philosophy to time and temporality, fandom ethnographies, and ethics. This article proposes to explore the boundaries of alien sex and the desire for alien others as represented in sci-fi role playing games, and their reinterpretation by fans. Science fiction role playing games in particular enable the production of sexual modalities outside of the constraints of heterosexual norms. Alien sex, animal sex, or monstrous sex are common tropes in fantasy and sci-fi media—the vampire, the werewolf, and monstrous non/in-humans are eroticized and construed conduits of a mainly female sexual desire. However, the example I would like to approach is slightly more radical, both in terms of execution and in terms of media audience response: examples of "alien sex" as illustrated in the Mass Effect video game series, whose canonical representation of alien-human romances invite some interesting questions about either the potential exacerbation, or the rendering-unintelligible of sexual difference, as well as about cross-species desire and about the ontology of the natural and the artificial.